2021
DOI: 10.3390/tomography7010002
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Disease Free Survival in Laryngeal and Hypopharyngeal Cancers Using CT Perfusion and Radiomic Features: A Pilot Study

Abstract: (1) Purpose: The objective was to evaluate CT perfusion and radiomic features for prediction of one year disease free survival in laryngeal and hypopharyngeal cancer. (2) Method and Materials: This retrospective study included pre and post therapy CT neck studies in 36 patients with laryngeal/hypopharyngeal cancer. Tumor contouring was performed semi-autonomously by the computer and manually by two radiologists. Twenty-six radiomic features including morphological and gray-level features were extracted by an i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Therefore, in addition to the current conventional treatments, a better understanding of the process of tumor occurrence and development can increase the possibility that gene therapy will become another new treatment method for hypopharyngeal cancer. Moreover, hypopharyngeal cancer shows low sensitivity to anticancer drugs, and its underlying mechanism is still unknown, which also leads to a poor prognosis and a low five-year survival rate for patients with hypopharyngeal cancer [ 27 , 28 ]. Therefore, research and development of new treatment methods to reduce the antichemotherapy effect of hypopharyngeal cancer and improve its five-year survival rate are considered to be a new challenge [ 29 ].…”
Section: Clinical Efficacy Of Hypopharyngeal Cancer Treatmentmentioning
confidence: 99%
“…Therefore, in addition to the current conventional treatments, a better understanding of the process of tumor occurrence and development can increase the possibility that gene therapy will become another new treatment method for hypopharyngeal cancer. Moreover, hypopharyngeal cancer shows low sensitivity to anticancer drugs, and its underlying mechanism is still unknown, which also leads to a poor prognosis and a low five-year survival rate for patients with hypopharyngeal cancer [ 27 , 28 ]. Therefore, research and development of new treatment methods to reduce the antichemotherapy effect of hypopharyngeal cancer and improve its five-year survival rate are considered to be a new challenge [ 29 ].…”
Section: Clinical Efficacy Of Hypopharyngeal Cancer Treatmentmentioning
confidence: 99%
“…Additionally, traditional radiographic response criteria, as used in this study, failed to capture treatment efficacy in its entirety. 18 Thus, improved noninvasive biomarkers are needed to help predict responses to induction therapy, ultimately leading to improvements in rates of organ preservation and overall survival.…”
Section: Discussionmentioning
confidence: 99%
“…CTPI can be used to evaluate the perfusion and vascularity of lesions in the lung and many other organs. [21][22][23][24][25][26][27][28] Wang et al 21 reported that parameters of CTPI (including BF, BV and PS but not MTT) of SPNs were significantly correlated with SPNs' microvessel density (MVD) and luminal vascular parameters such as luminal vascular number (LVN), luminal vascular area (LVA), and luminal vascular perimeter (LVP). Huang et al 22 analyzed the CT perfusion parameters (BF, BV, MTT, and PS) and the microvessel parameters (MVD, LVN, LVA, and LVP) in the non-small cell lung cancer (NSCLC) patients with and without lymph node metastasis.…”
Section: Ctpi In Evaluating Spnsmentioning
confidence: 99%